ICT in schools in Brazil: Challenges of implementation, modernization and inclusion of education system through digital media from the perspective of experts from inclusion, education and human rights sectors - de-la-Higuera-Amato, Cibelle A; Farinazzo-Martins, Valéria; Eliseo, Maria Amelia; Frango-Silveira, Ismar (Memorias y Boletines de la Universidad del Azuay, 2020)
This paper aims to discuss some issues about ICT used in the teaching, learning and inclusion process: implementation, odernization, barriers and challenges. Therefore, three experts with extensive experience in three different areas were interviewed: an inclusion specialist, one in computers in education and one in human rights. The data were analyzed using the interpretative paradigm of qualitative research, and presented respondents’ experiences of implementing ICT in education. Keywords: inclusion, ICT in education, learning, people with disabilities.